TEACHER PARTICIPATION IN EDUCATION ADMINISTRATION - Hasrat A Aimang; Haluti, Armin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
The essence is that the foundation in the management of education in achieving instructional goals, the participation of teachers in organizing educational administration is needed. This study aims to examine teacher participation in educational administration at SMP Negeri 5 Luwuk. Educational administration is an important aspect in supporting the success of the teaching and learning process in schools. This study used a descriptive qualitative method involving 15 respondents consisting of teachers at SMP Negeri 5 Luwuk. Data were collected through interviews, observations and document analysis. The results show that the level of teacher participation in education administration varies, covering aspects of planning, organizing, implementing and evaluating. Factors influencing teachers' participation include understanding the importance of education administration, workload and support from school leaders. The study also identified the challenges teachers face in carrying out administrative tasks as well as strategies to improve their participation. The findings can serve as input for schools and education stakeholders in an effort to improve the quality of education administration at the junior secondary school level.